2012
DOI: 10.7314/apjcp.2012.13.10.4979
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Breast Cancer among Women in Eastern India: A Tertiary Hospital Based Case Control Study

Abstract: Aim: Breast cancer is one of the most common cancers of women in India with high fatality rate. Over a 1 year study period 105 consecutive biopsy or fine needle aspiration cytology confirmed breast cancer patients were interviewed by direct questionnaire method regarding risk factors attending Surgery and Radiotherapy OPD of Medical College Kolkata, West Bengal while taking other 105 patients attending Surgery Department for some other disease as controls. The data were compiled in MS Excel 2007 and analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 8 publications
6
29
1
1
Order By: Relevance
“…According to some researchers, it is associated with an increased tendency to postpone the first childbirth, combined with a low parity and short duration of breastfeeding in developed countries (Kobayashi et al, 2012). There is another trend in Kazakhstan: adverse living conditions of lower social strata of population living in rural areas is a risk factor for development of BC, which is consistent with some recent publications (Nosheen Fatima et al, 2010;Das et al, 2012). Several studies mention the role and significance of such factors like abortion, hereditary predisposition, and chronic stress (Collaborative Group on Hormonal Factors in Breast Cancer, 2004;Santos et al, 2009;Amir et al, 2010;Antonova et al, 2011).…”
Section: Discussionsupporting
confidence: 72%
“…According to some researchers, it is associated with an increased tendency to postpone the first childbirth, combined with a low parity and short duration of breastfeeding in developed countries (Kobayashi et al, 2012). There is another trend in Kazakhstan: adverse living conditions of lower social strata of population living in rural areas is a risk factor for development of BC, which is consistent with some recent publications (Nosheen Fatima et al, 2010;Das et al, 2012). Several studies mention the role and significance of such factors like abortion, hereditary predisposition, and chronic stress (Collaborative Group on Hormonal Factors in Breast Cancer, 2004;Santos et al, 2009;Amir et al, 2010;Antonova et al, 2011).…”
Section: Discussionsupporting
confidence: 72%
“…The findings are similar to study conducted by Kamath R et al In the studies conducted by Joseph M. Ramon et al, Gajalakshmi et al and Soumen Das et al, early age at first full term pregnancy has a protective effect from breast cancer. [3,7,18,19] The present study showed significant unadjusted risk of breast cancer for the women who have breastfed for ≤6months (OR=2.57; 95% CI: 0.94-7.04). There was statistically no significant association between duration of breast feeding and breast cancer risk (p=0.057).…”
Section: Discussionmentioning
confidence: 48%
“…In our present study, the age at menarche in the older patients was one year later than the younger group. Menarche at a relatively early age is associated with an increased risk for breast cancer (Das et al, 2012). Moreover, breast cancer was more common in young women of urban areas perhaps due to adaptation of a more sedentary life style.…”
Section: Discussionmentioning
confidence: 99%